IMPROVING THE ABILITY TO RECOGNIZE HIJAIYAH LETTERS THROUGH TILAWATI METHOD AT TK ISLAM ATTAQWA SETU BEKASI - Titin Kusayang; Intan Sukreni (AMIN: International Journal of Islamic Education and Knowledge Integration, 2023)
Early childhood class B at At-Taqwa Setu Bekasi Islamic Kindergarten uses the Tilawati method to improve their understanding of Hijaiyah letters. The goal of this study is to determine whether teaching the tilawati technique to young children in class B TK At-Taqwa Setu Bekasi will improve their ability to recognize hijaiyah letters. This study employs the classroom action research methodology. Two cycles, each with two sessions, were used for this study. The study's participants were 22 kids from class B of At-Taqwa Islamic Kindergarten. The typical student has a 0% success rate during the pre-cycle and is included in the undeveloped (BB) criterion. The early childhood class B at Islamic Kindergarten At-Taqwa Setu Bekasi found that adopting the tilawati method to teach kids to recognize hijaiyah letters dramatically increased pupils' ability in this area. The study's end results showed that student achievement in cycle I was 27% whereas it was 100% in cycle II. This supports the assertion that there was a significant increase from cycle I to cycle II.